Analisis Penanganan Kargo Miscellanous Dangerous Goods pada Regulated Agent di PT. Buana Citradjaya Dirgantara - Kartini Benga Wuan; Zenita Kurniasari (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
One of the functions of air transportation is to transport goods from one place to another. One type of goods is class 9 cargo called Miscellanous Dangerous Goods. This study aims to determine the handling of Miscellanous Dangerous Goods cargo in Regulated agents at PT. Buana Citradjaya Dirgantara, what problems occur in the process of handling Miscellanous Dangerous Goods cargo at Regulated Agents at PT. Buana Citradjaya Dirgantara and efforts to overcome the constraints of handling Miscellanous Dangerous Goods cargo at Regulated Agents at PT. Buana Citradjaya Dirgantara This study used a qualitative method with data sources in the form of primary data and secondary data. Data collection techniques include observation, interviews, and documentation. Data validity techniques use source triangulation and triangulation techniques. Data analysis techniques used include data reduction, data presentation, and conclusions. The result of this study is that Miscellanous Dangerous Goods cargo handling has been carried out in accordance with SOPs or applicable regulations. Officers carry out the flow of delivery, inspection, and delivery in accordance with applicable SOPs and regulations. Obstacles in handling Miscellanous Dangerous Goods cargo at Regulated Agents at PT. Buana Citradjaya Dirgantara, including the lack of knowledge of prospective shippers regarding Miscellanous Dangerous Goods cargo delivery documents and the content of Miscellanous Dangerous Goods cargo which can make officers injured and lack of storage of Miscellanous Dangerous Goods so that they are united with other goods can endanger officers and damage other goods. Efforts to Handle Miscellanous Dangerous Goods Cargo at Regulated Agents at PT. Buana Citradjaya Dirgantara, namely conducting more socialization to the sender of goods regarding the documents needed in shipping Miscellanous Dangerous Goods cargo and officers should be more focused and use personal protective equipment such as gloves and Dangerous Goods goggles prepare a special place to store Miscellanous Dangerous Goods cargo so as not to endanger officers or other goods.